(untitled) (International Journal of Current Engineering and Technology, 2014)
In this paper, the modeling of the Direct Torque Control (DTC) system of permanent magnet synchronous motor (PMSM) based on Matlab/Simulink environment is presented. Simulation results are introduced to predict the motor drive system performance and the effect of PI-like fuzzy controller parameters on speed response in this system . The simulation results show that the torque ripple can be reduced by narrowing the torque hysteresis loops width.